A change in brain white matter after shunt surgery in idiopathic normal pressure hydrocephalus: a tract-based spatial statistics study. Issue 1 (December 2017) - Kanno, Shigenori; Saito, Makoto; Kashinoura, Tomohito; Nishio, Yoshiyuki; Iizuka, Osamu; Kikuchi, Hirokazu; Takagi, Masahito; Iwasaki, Masaki; Takahashi, Shoki; Mori, Etsuro
Abstract Background The aim of this study was to elucidate changes in cerebral white matter after shunt surgery in idiopathic normal pressure hydrocephalus (INPH) using diffusion tensor imaging (DTI). Methods Twenty-eight consecutive INPH patients whose symptoms were followed for 1 year after shunt placement and 10 healthy control (HC) subjects were enrolled. Twenty of the initial 28 INPH patients were shunt-responsive (SR) and the other 8 patients were non-responsive (SNR). The cerebral white matter integrity was detected by assessing fractional anisotropy (FA) and mean diffusivity (MD). The mean hemispheric DTI indices and the ventricular sizes were calculated, and a map of these DTI indices was created for each subject. The DTI maps were analysed to compare preshunt INPH with HC and preshunt INPH with 1 year after shunt placement in each INPH group, using tract-based spatial statistics. We restricted analyses to the left hemisphere because of shunt valve artefacts. Results The ventricles became significantly smaller after shunt placement both in the SR and SNR groups. In addition, there was a significant interaction between clinical improvement after shunt and decrease in ventricular size. Although the hemispheric DTI indices were not significantly changed after shunt placement, there was a significant interaction between clinical improvement and increase in hemispheric MD. Compared with the HC group, FA in the corpus callosum and in the subcortical white matter of the convexity and the occipital cortex was significantly lower in SR at baseline, whereas MD in the periventricular and peri-Sylvian white matter was significantly higher in the SR group. Compared with the pre-operative images, the post-operative FA was only decreased in the corona radiata and only in the SR group. There were no significant regions in which DTI indices were altered after shunt placement in the SNR group. Conclusions Brain white matter regions in which FA was decreased after shunt placement were in the corona radiata between the lateral ventricles and the Sylvian fissures. This finding was observed only in shunt-responsive INPH patients and might reflect the plasticity of the brain for mechanical pressure changes from the cerebrospinal fluid system.